2023
DOI: 10.1002/alz.13439
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and risk of incident dementia in UK Biobank

Danial Qureshi,
Jennifer Collister,
Naomi E. Allen
et al.

Abstract: INTRODUCTIONThe association between metabolic syndrome (MetS) and incident dementia remains inconclusive.METHODSIn 176,249 dementia‐free UK Biobank participants aged ≥60 years at baseline, Cox proportional‐hazards models were used to investigate the association between MetS and incident dementia. MetS was defined as the presence of ≥3 of the following: elevated waist circumference, triglycerides, blood pressure, blood glucose, and reduced high‐density lipoprotein cholesterol.RESULTSOver 15 years of follow‐up (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…A study conducted by researchers from the University of Oxford involved a 15-year follow-up on 176,000 participants without dementia. The study found that metabolic syndrome was associated with a 12% increased risk of developing dementia (56). These findings were corroborated by a research team from South Korea who also observed a connection between metabolic disturbances and an elevated risk of dementia (57).…”
Section: Discussionsupporting
confidence: 56%
“…A study conducted by researchers from the University of Oxford involved a 15-year follow-up on 176,000 participants without dementia. The study found that metabolic syndrome was associated with a 12% increased risk of developing dementia (56). These findings were corroborated by a research team from South Korea who also observed a connection between metabolic disturbances and an elevated risk of dementia (57).…”
Section: Discussionsupporting
confidence: 56%
“…Various components of MetS have been found in crosssectional and longitudinal studies to cause decreases in learning memory, attention, visuospatial and executive functions, and processing speed (14,15). A 15-year follow-up analysis of 176,000 non-demented participants found that MetS led to a 12% increased risk of developing all-cause dementia (16).…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors share common underlying causal mechanisms, resulting in a complex interplay that characterizes MetS [ 1 ]. Numerous studies have been conducted to investigate the definition, prevalence, and related features of MetS, as well as to explore its connection with cardiovascular disease (CVD) [ 2 ], diabetes mellitus (DM) [ 3 ], and dementia [ 4 ]. MetS is widely widespread in several nations such as the United States [ 5 ], China [ 6 ], and is associated with increased all-cause mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%